30년 전 성공적인 발목 유합술 이후 발생한 주변 관절 관절염 환자에 대한 발목 인공관절 전환술: 증례 보고 - 이정환; 강태병; 유태욱; 이동오; 서상교; Jeong Hwan Lee; Taebyeong Kang; Tae Wook Yoo; Dongoh Lee; Sang Gyo Seo (대한족부족관절학회지, 2025)
This paper reports the clinical efficacy of conversion total ankle arthroplasty as an intervention for adjacent joint arthritis following ankle arthrodesis. The case involved a 61-year-old male with a 30-year history of successful ankle fusion who presented with progressive ankle pain with a 2-year duration. The surgical approach included the conversion of ankle arthrodesis to total ankle replacement combined with talo-navicular joint arthrodesis to address the symptomatic adjacent joint arthritis. The postoperative follow-up at 2 years revealed significant pain reduction and enhanced functional outcomes. The findings suggested that conversion to total ankle replacement is a viable therapeutic alternative for patients with post-arthrodesis pain. In addition, fibula-preserving ankle arthrodesis techniques may help facilitate potential subsequent conversion to total ankle arthroplasty in cases where ankle fusion is indicated.